143 STROMAL TENASCIN C IN BREAST CANCER: EFFECTS ON MAMMARY EPITHELIAL TISSUE ARCHITECTURE. (1st January 2006) - Taraseviciute, A.; Vincent, B. T.; Jones, P.
Abstract : Breast cancer is the most common type of female cancer, affecting approximately 1 in 8 US women. Despite numerous advances in breast cancer screening programs and treatment, it remains the second leading cause of cancer deaths in women. Although the majority of breast cancer research has focused on understanding and targeting transformed breast epithelial cells, recently, a large body of literature has revealed the important role of the surrounding breast tumor stroma in cancer initiation and progression. The stroma comprises myoepithelial cells (that surround the epithelial cell-lined ducts of the breast), fibroblasts, and the extracellular matrix (ECM). Our studies have focused on the ECM glycoprotein tenascin C (TN-C), which is generally absent in the normal human adult breast stroma. Initially, the expression pattern of TN-C was investigated using immunohistochemistry in breast cancer tissue microarrays encompassing ≈240 patient samples, which revealed strong stromal TN-C expression in the vast majority of infiltrating ductal carcinoma cases, as well as other, less common, breast cancer types. Having established the induction of TN-C in human breast cancer stroma, we used 3-D organotypic cultures of human MCF-10A mammary epithelial cells to model how TN-C might affect epithelial cell behavior. Accordingly, MCF-10A cells were cultured for 3-8 days in a reconstituted basement membrane cocktail (Matrigel), with or without purified human TN-C protein. Changes in 3-D epithelial cell cultures were monitored using phase contrast, immunofluorescence, and confocal microscopy, which revealed increased proliferation (determined by Ki-67), decreased apoptosis (determined by activated caspase-3), and disrupted polarity and adhesion (determined by laminin-5, integrin alpha6, beta-catenin, and FAK), in the presence of TN-C. Furthermore, we developed a novel algorithm to objectively quantify the effects of TN-C on epithelial cell architecture and used computational modeling to obtain 3-D reconstructions of epithelial structures. Computational analysis revealed a two-fold increase in surface roughness in 3-D mammary epithelial cell cultures in the presence of TN-C. Our findings reveal that stromal TN-C is widely expressed in the majority of breast cancer cases and exerts a profound effect on normal human mammary epithelial tissue architecture by disrupting cell-cell adhesion and increasing proliferation.